River, Coastal and Estuarine Morphodynamics: RCEM 2007, Two Volume Set 2007
DOI: 10.1201/noe0415453639-c2
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of a morphodynamic modeling system applied to a Portuguese tidal inlet

Abstract: Coastal area morphodynamic models are prone to severe errors arising from various sources, including: (1) the use of empirical sediment transport formulae (Pinto et al., 2006); (2) the reliability of the data used to feed the models; (3) the use of simplifying physical assumptions; (4) the error propagation between the various modules. Since these errors can be significant, the usefulness and credibility of morphodynamic simulations require a thorough understanding of their uncertainty. This paper addresses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The performance of MORSYS2D was assessed in the morphodynamic simulation forced both by current and waves of the Óbidos lagoon and is described in Oliveira et al (2004). The morphodynamic of this lagoon and its inlet have been studied and published in several works: Oliveira (2006, 2007); Bertin et al (2007Bertin et al ( , 2009a; Fortunato et al (2009). In these studies the authors concluded, that the sediment grain size and the choice of the empirical sediment transport formulae affect the morphological predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of MORSYS2D was assessed in the morphodynamic simulation forced both by current and waves of the Óbidos lagoon and is described in Oliveira et al (2004). The morphodynamic of this lagoon and its inlet have been studied and published in several works: Oliveira (2006, 2007); Bertin et al (2007Bertin et al ( , 2009a; Fortunato et al (2009). In these studies the authors concluded, that the sediment grain size and the choice of the empirical sediment transport formulae affect the morphological predictions.…”
Section: Introductionmentioning
confidence: 99%